Psychosocial Support for Healthcare Workers During the COVID-19 Pandemic - Tomlin, Jack; Dalgleish-Warburton, Bryan; Lamph, Gary (Frontiers in Psychology, 2020)
The novel corona virus disease COVID-19 was first diagnosed in humans in Wuhan, China in December 2019. Since then it had become a global pandemic. Such a pandemic leads to short- and long-term mental health burden for healthcare workers. Recent surveys suggest that rates of psychological stress, depression, anxiety, and insomnia and will be high for this group. Numerous organisations have since released guidance on how both healthcare workers and the general public can manage the mental health burden. However, these recommendations focus on specific healthcare workers (e.g. nurses or psychologists), are often not evidence-based, and typically do not situate guidance within a phased model that recognises countries are at different stages of the COVID-19 pandemic. In this perspective paper we propose a phased model of mental health burden and responses. Building on work by the Intensive Care Society and the Royal College of Psychiatrists in the United Kingdom, we present a model that demonstrates how both staff and organisations might respond to the likely stressors that might occur at preparation-, pre-, initial and core-, and longer-term-phases of the pandemic. Staff within countries at different stages of the COVID-19 pandemic will be able to use this model. We suggest practical tips for both healthcare workers and organisations and embed this within up-to-date scientific literature. The phased model of mental health burden and responses can be a helpful guide for both staff and organisations operating at different stages of the pandemic.